2003
DOI: 10.1097/00004836-200302000-00008
|View full text |Cite
|
Sign up to set email alerts
|

An Association Between Helicobacter pylori Infection and Serum Vitamin B12 Levels in Healthy Adults

Abstract: The higher prevalence of H. pylori infection among subjects with serum vitamin B12 levels that are within the lower end of the normal range suggests a causal relationship between H pylori infection and vitamin B12 levels in healthy adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…Food-bound cobalamin malabsorption results from conditions that impair the secretion of gastric acid and pepsin required for the release of cobalamin from proteins in food [25,26]. Adult studies performed in H. pylori-infected patients revealed a high rate of vitamin B 12 deficiency [16][17][18][19][20]. The mechanism of vitamin B 12 malabsorption caused by H. pylori infection is unclear, but it may be due to the effect of H. pylori on gastric acid secretion.…”
Section: H Pylori Infection and Vitamin B 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Food-bound cobalamin malabsorption results from conditions that impair the secretion of gastric acid and pepsin required for the release of cobalamin from proteins in food [25,26]. Adult studies performed in H. pylori-infected patients revealed a high rate of vitamin B 12 deficiency [16][17][18][19][20]. The mechanism of vitamin B 12 malabsorption caused by H. pylori infection is unclear, but it may be due to the effect of H. pylori on gastric acid secretion.…”
Section: H Pylori Infection and Vitamin B 12mentioning
confidence: 99%
“…Additionally, Kurekci et al [15] showed that the eradication of H. pylori infection without iron treatment led to the resolution of iron deficiency in children. Fewer studies, performed in adults, also revealed positive relations between H. pylori and vitamin B 12 deficiency [16][17][18][19][20], whereas no obvious relation was detected between H. pylori and serum vitamin B 12 levels in a study performed without endoscopy and biopsy in children [21]. A positive relation was also reported between H. pylori and folate deficiency in adults [1].…”
Section: Introductionmentioning
confidence: 99%
“…pylori not only causes a local gastric response but also produces systemic effects: defects particularly in vitamin B12 absorption [15][16][17], alterations in growth hormone (GH) levels [18][19][20], increments in serum and mucosal levels of cytokines [21,22], and changes in estrogen levels [23] have all been reported in H. pylori-positive (+) individuals. Although it is well known that all these changes have the potential to influence bone remodeling, there are limited data on the alterations in biochemical markers of bone metabolism in patients with H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…This condition impairs the absorption of vitamin B 12 -with consequent hyper-homocysteinemia [50] and a correlation between augmented systemic levels of homocysteine and SSHL development is known.…”
Section: Discussionmentioning
confidence: 99%